Nasal Intermittent Positive Pressure Ventilation and Bronchopulmonary Dysplasia Among Very Preterm Infants Never Intubated During the First Neonatal Admission: A Multicenter Cohort Study - Avila-Alvarez, Alejandro; García-Muñoz Rodrigo, Fermín; Solís-García, Gonzalo; Pertega-Diaz, Sonia; Sánchez Luna, Manuel; Iriondo-Sanz, Martin; Elorza Fernandez, Dolores; Zozaya, Carlos (Frontiers in Pediatrics, 2022)
While non-invasive positive-pressure ventilation (NIPPV) is increasingly used as a mode of respiratory support for preterm infants, it remains unclear whether this technique translates into improved respiratory outcomes. We assessed the association between NIPPV use and bronchopulmonary dysplasia (BPD)-free survival in never intubated very preterm infants. Methods: This multicenter cohort study analyzed data from the Spanish Neonatal Network SEN1500 corresponding to preterm infants born at <32 weeks gestational age and <1,500 grams and not intubated during first admission. The exposure of interest was use of NIPPV at any time and the main study outcome was survival without moderate-to-severe BPD. Analyses were performed both by patients and by units. Primary and secondary outcomes were compared using multilevel logistic-regression models. The standardized observed-to-expected (O/E) ratio was calculated to classify units by NIPPV utilization and outcome rates were compared among groups. Results: Of the 6,735 infants included, 1,776 (26.4%) received NIPPV during admission and 6,441 (95.6%) survived without moderate-to-severe BPD. After adjusting for confounding variables, NIPPV was not associated with survival without moderate-to-severe BPD (OR 0.84; 95%CI 0.62–1.14). A higher incidence of moderate-to-severe BPD-free survival was observed in high- versus very low-utilization units, but no consistent association was observed between O/E ratio and either primary or secondary outcomes. Conclusion: NIPPV use did not appear to decisively influence the incidence of survival without moderate-to-severe BPD in patients managed exclusively with non-invasive ventilation.